INFLUENCE DEBT EQUITY RATIO, MARKET RISKS, AND GOOD CORPORATE GOVERNANCE ON SHARE PRICES - Budiono (Journal of Business, Management, & Accounting, 2021)
This study aims to determine the effect of Debt Equity Ratio, Market Risk, and Good Corporate Governance on Stock Prices. In this study, Debt, Equity ratio, market risk, and good corporate governance as independent variables, and stock prices as the dependent variable. The samples taken are companies listed on the Jakarta Stock Exchange and participating in CGPI 2007-2010. Data processing and analysis were carried out using the SmartPLS program. The results of this study indicate that the Debt Equity Ratio variable has no effect on stock prices, market risk has no effect on stock prices, and good corporate governance has an effect on stock prices. Together, the Debt Equity Ratio, Market Risk, and Good Corporate Governance have an effect of 25.7%.